Transcriptional Up-Regulation and Activation of Initiating Caspases in Experimental Glaucoma - Huang, Wei (American Society for Investigative Pathology, 2005)
In glaucoma, retinal ganglion cells (RGCs) die by apoptosis, generally attributed to an elevated intraocular pressure (IOP). We now describe the impact of elevated IOP in the rat on expression of caspase 8 and caspase 9, initiators of the extrinsic and intrinsic caspase cascades, respectively. Activation of both caspases was demonstrated by the presence of cleaved forms of the caspases and the detection of cleaved Bid and PARP, downstream consequences of caspase activation. Surprisingly, the absolute level of procaspase 9 was also elevated after 10 days of increased IOP. To examine the cause of increased levels of the procaspase, we used laser capture microdissection to capture Fluorogold back-labeled RGCs and real-time polymerase chain reaction to measure mRNA changes of initiating caspases. The mRNA levels of both caspase 8 and caspase 9 were increased specifically in RGCs. These data suggest that elevated IOP activates a transcriptional up-regulation and activation of initiating caspases in RGCs and triggers apoptosis through both extrinsic and intrinsic caspase cascades.